Association between subclinical left ventricular ejection fraction and platelet-to-lymphocyte ratio in patients with peritoneal dialysis - Duan, Yingjie; Peng, Zhong; Zhong, Shuzhu; Huang, Hong; He, Zhangxiu (Frontiers in Medicine, 2022)
Background Reduced left ventricular ejection function (LVEF) was associated with increased mortality in patients with peritoneal dialysis (PD) in Asia and the United States of America. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were correlated with LVEF in PD. However, little information is available regarding the relationship between monocyte-to-lymphocyte ratio (MLR), left ventricular ejection fraction (LVEF), and the use of NLR, PLR, and MLR in predicting left ventricular systolic dysfunction (LVSD) in patients with PD. Methods All 181 patients with PD were enrolled between 2014 and 2021 from the Nephrology Department of the First Affiliated Hospital of the University of South China. Demographic features, clinical characteristics, laboratory values, and echocardiographic parameters were collected. Results The mean age of patients with PD was 47.4 ± 12.6, and 90 (49.7%) of the patients were men. LVEF showed a negative correlation with PLR (r = −0.200, p = 0.007) and MLR (r = −0.146, p = 0.049). The levels of NLR, PLR, and MLR were elevated in patients with PD with LVSD compared with those without (all p < 0.05). PLR (OR 4.331, 95% CI: 1.223, 15.342) and albumin (OR 13.346, 95% CI: 3.928, 45.346) were significantly associated with LVSD patients with PD in the multivariate logistic analysis. For differentiating patients with PD with LVSD, optimal cutoffs of NLR, PLR, MLR, and albumin were 4.5 (sensitivity: 76.7%, specificity: 55.0%, and overall accuracy: 58%), 202.6 (sensitivity: 66.7%, specificity: 69.5%, and overall accuracy: 69%), 0.483 (sensitivity: 53.3%, specificity: 72.8%, and overall accuracy: 30%), and 34.6 (sensitivity: 72.2%), respectively. Conclusions Our results revealed that PLR was better than NLR, MLR, and albumin in predicting LVSD in PD.